Perancangan Sistem Pencatatan Dan Laporan Keuangan Berbasis Website Pada Leebra Laundry - Lita Christina; Umi Fitria Ulfa (Universitas Internasional Batam, 2021)
This study aims to design a recording system and financial reports at Leebra Laundry with functions according to company needs. Data collection methods used are through observation and interviews, both directly and indirectly with business owners to find out the problems that arise at the Leebra Laundry. In this study, Leebra Laundry has problems with the recording system and business financial reports. Leebra Laundry still uses a manual recording system in books. The recording is only limited to income and expenditure transactions. Therefore, the author wants to carry out the practical work at Leebra Laundry by designing a system of recording and financial reports based on a website system. The making of this system uses existing lateral framework-free templates and is tailored to the needs of Lebra Laundry. In the implementation of this practical work, the owner can use the accounting system developed by using the website to reduce errors in recording transactions and provide the financial information needed. The next practical work recommendation is to make the best use of a computerized system, especially in the field of accounting, in order to produce better financial reports than the existing ones and also to add other financial reports that the authors have not made.